MiR-181d-5p Targets KLF6 to Improve Ischemia/Reperfusion-Induced AKI Through Effects on Renal Function, Apoptosis, and Inflammation - Zhang, Yue; Li, Chenyu; Guan, Chen; Zhou, Bin; Wang, Lin; Yang, Chengyu; Zhen, Li; Dai, Jie; Zhao, Long; Jiang, Wei; Xu, Yan (Frontiers in Physiology, 2020)
Renal tubular epithelial cell (RTEC) death and renal interstitial inflammation are the most crucial pathophysiological changes in acute kidney ischemia/reperfusion injury (IRI). The microRNA (miR)-181d family plays diverse roles in cell proliferation, apoptosis and inflammation, but its renal target and potential role in IRI are unknown. Here, we showed that the expression of miR-181d-5p decreased in a renal cell (HK-2) model of hypoxia/reoxygenation (H/R) injury and a mouse model of renal IRI. Mechanistically, KLF6 was predicted as a new potential target gene of miR-181d-5p through bioinformatic analysis and luciferase reporter assay verification. After renal I/R, overexpression of miR-181d-5p significantly attenuated the level of KLF6 and inhibited inflammatory mediators, reducing apoptosis and further improving renal function. Pivotal NF-κB signaling pathways regulated the inflammatory response. In conclusion, miR-181d-5p upregulation produced protective antiapoptotic and anti-inflammatory effects against IRI in kidneys in vivo and H/R injury in HK-2 cells in vitro, and these effects were achieved by targeted inhibition of KLF6. Thus, our results provide novel insights into the molecular mechanisms associated with IRI and a potential novel therapeutic target.